PENERAPAN DIGITAL MARKETING PRODUK KEMASAN MIE CELOR POLIGON PROMOSI ONLINE PROGRAM MBKM MAHASISWA INDO GLOBAL MANDIRI - Fadhilsyah, Muhammad; Siti Zahara, Meisin; Hertati, Lesi; Terttiaavini; Heryati, Agustina; Asmawati (Transpublika Publisher, 2021)
Palembang City is renowned not only for its songkat cloth but also for its specialty foods, including noodle soup. The numerous culinary micro, small, and medium enterprises (MSMEs) in the city require guidance to succeed in their businesses. They need assistance in sourcing capital, developing strategies to cope with intense competition, and improving product packaging through online promotion. One such MSME is Mie Celor Poligon, located in Bukit Sejahtera Housing, Big Door Gate, Ilir Barat 1 Sub-District, Palembang City. This community service activity aims to support these MSMEs in surviving the current situation by enabling them to enhance their product packaging online, thereby increasing sales during the pandemic. Their previous packaging was overlooked and unappealing. The MSMEs currently manage online promotion and sales through limited face-to-face and online transactions, relying heavily on personal information to maximize bookings. This educational program involves counseling and coaching these MSMEs to improve their practices.